Analysis of Children's Fairytale Media Needs Macromedia Flash-Based Local Wisdom For Elementary School Students - Siti Anafiah; Dyan Indah Purnama Sari (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study aims to analyze the need for children's fairy tales containing local wisdom based on macromedia flash for elementary school students. This type of research is qualitative research. This study intends to reveal the needs analysis for children's fairy tales containing local wisdom based on macromedia flash for students at SD Taman Muda IP Yogyakarta. The research subjects were fourth grade students. This research data collection technique using participant observation, interviews, and documentation. Data analysis in this study used an interactive model of data analysis. The analysis consists of three activity lines, namely: data reduction, data presentation, and conclusion / verification. From the results of the needs analysis at SD Taman Muda IP Yogyakarta, it was found that this study began with a needs analysis by identifying the basic competencies contained in thematic learning Indonesian content. In the Indonesian language content, material about fairy tales is found in theme 4 Sharing Work, namely KD 3.5 Describing personal opinions about the contents of literary books (stories, fairy tales, and so on). KD 4.5 Communicating personal opinions about the contents of selected and read literary books orally and in writing supported by reasons. From the basic competency analysis of some of the learning content, researchers can develop innovative media, namely children's fairy tales containing local wisdom based on Macromedia Flash.